Anthrax lethal toxin (LeTx) neutralization by PA domain specific antisera. (1st December 2017) - Verma, Monika; Suryanarayana, Nagendra; Tuteja, Urmil; Thavachelvam, Kulanthaivel; Rao, M.K.; Bhargava, Rakesh; Shukla, Sangeeta
Abstract: Anthrax associated causalities in humans and animals are implicated mainly due to the action of two exotoxins that are secreted by the bacterium Bacillus antharcis during the infection. These exotoxins comprise of three protein components namely protective antigen (PA), lethal factor (LF) and edema factor (EF). The protective antigen is the common toxin component required to form both lethal toxin (LeTx) and edema toxin (EdTx). The LeTx is formed, when PA combines with LF and EdTx is formed when PA combines with EF. Therapeutic interventions aiming to neutralize these key effectors of anthrax pathology would therefore, provide an effective means to counter the toxicity imposed by the anthrax toxins on the host. The present work describes the lethal toxin neutralization potential of polyclonal antisera developed against the individual domains of the protective antigen component of the anthrax toxin. The individual domains were produced as recombinant proteins in E. coli and validated with peptide mass fingerprinting by MALDI-TOF analysis and corresponding mice polyclonal antisera by western blotting. Each domain specific antibody titre and isotype was ascertained by ELISA. The isotyping revealed the predominance of IgG1 isotype. The toxin neutralizing potential of these domain specific antisera were evaluated by in-vitro cell viability MTT assay, employing J774.1 mouse macrophage cell line against LeTx (0.25 μg ml −1 PA and 0.125 μg ml −1 LF concentrations). Among the four domain specific antisera, the antiserum against PA domain IV could neutralize LeTx with high efficiency. No significant neutralization of LeTx was observed with other domain specific antibodies. Results indicate that antibodies to r-PA domain IV could be explored further as therapeutic anti toxin molecule along with appropriate antibiotic regimens against anthrax. Highlights: Individual PA domains were cloned and expressed in E. coli . Recombinant PA domains were purified and authenticated by MALDI-TOF. PA domain specific antisera were generated and assessed for their isotypes. In vitro lethal toxin neutralization potential of domain specific antisera was evaluated on J774.1 mouse macrophage cell line. PA DIV specific antisera were found to be superior when compared to other domains antisera.